KARAKTERISTIK ORGANOLEPTIK DAN PROKSIMAT MIE BASAH DENGAN PENAMBAHAN TEPUNG TERIPANG PASIR (Holothuria scabra) - Vatma, Ona Sri; Ansharullah, Ansharullah; Asnani, Asnani (Jurnal Sains dan Teknologi Pangan, 2021)
ABSTRACTThe purpose of this study was to determine the effect of the addition of sea cucumber flour on the organoleptic and proximate characteristics of wet noodles. This study consisted of four treatments, namely without the addition of sand sea cucumber flour (T0), the addition of 5% sea cucumber flour (T1), the addition of 10% sea cucumber flour (T2), and the addition of 15% sea cucumber flour (T3). The analyzed parameters were organoleptic and physicochemical values. This study used a completely randomized design (CRD). Data were analyzed using Analysis of Variance (ANOVA) and continued with Duncan's Multiple Range Test (DMRT) at a 95% confidence level. The results show that the effect of adding sand sea cucumber flour had a very significant effect on organoleptic assessment in T1 treatment (95% wheat flour: 5% sea cucumber flour) with preference scores of color, aroma, taste, and texture reached 4.03 (like), 4.06 (like), 3.91 (like), and 4.06 (like). Proximate analysis of the best treatment shows that it contained 50.12% water, 1.18% ash, 0.20% fat, 7.23% protein, and 41.75% carbohydrate. The results show that the product met the standard of SNI 01-2987-1992 for ash, fat, and protein contents. Keywords: Sea Cucumber, Wet NoodlesABSTRAKTujuan penelitian ini untuk menentukan pengaruh penambahan tepung teripang pasir terhadap karakteristik organoleptik dan proksimat mie basah. Penelitian ini terdiri dari empat perlakuan yaitu tanpa penambahan tepung teripang pasir (T0), penambahan tepung teripang pasir 5% (T1), penambahan tepung teripang pasir 10% (T2), dan penambahan tepung teripang pasir 15% (T3), lalu dianalisis terhadap nilai organoleptik dan fisikokimia. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL). Data di analisis menggunakan Analysis of Varian (ANOVA) dan dilanjutkan dengan uji Duncan’s Multiple Range Test (DMRT) pada taraf kepercayaan 95%. Hasil penelitian menunjukkan bahwa pengaruh penambahan tepung teripang pasir berpengaruh sangat nyata terhadap penilaian organoleptik pada perlakuan T1 (tepung terigu 95% : tepung teripang pasir 5%) sebesar warna 4.03 (suka), aroma 4.06 (suka), rasa 3.91 (suka), dan tekstur 4.06 (suka). Analisis proksimat perlakuan terbaik diperoleh nilai kadar air 50.12%, kadar abu 1.18%, kadar lemak 0.20%, kadar protein 7.23% dan kadar karbohidrat 41.75%. Berdasarkan hasil penelitian nilai kadar abu, kadar lemak, dan kadar protein telah memenuhi SNI 01-2987-1992.Kata kunci: Teripang Pasir, Mie Basah